Mitochondria in Injury, Inflammation and Disease of Articular Skeletal Joints - Early, James Orman; Fagan, Lauren E.; Curtis, Annie M.; Kennedy, Oran D. (Frontiers in Immunology, 2021)
Inflammation is an important biological response to tissue damage caused by injury, with a crucial role in initiating and controlling the healing process. However, dysregulation of the process can also be a major contributor to tissue damage. Related to this, although mitochondria are typically thought of in terms of energy production, it has recently become clear that these important organelles also orchestrate the inflammatory response via multiple mechanisms. Dysregulated inflammation is a well-recognised problem in skeletal joint diseases, such as rheumatoid arthritis. Interestingly osteoarthritis (OA), despite traditionally being known as a ‘non-inflammatory arthritis’, now appears to involve an element of chronic inflammation. OA is considered an umbrella term for a family of diseases stemming from a range of aetiologies (age, obesity etc.), but all with a common presentation. One particular OA sub-set called Post-Traumatic OA (PTOA) results from acute mechanical injury to the joint. Whether the initial mechanical tissue damage, or the subsequent inflammatory response drives disease, is currently unclear. In the former case; mechanobiological properties of cells/tissues in the joint are a crucial consideration. Many such cell-types have been shown to be exquisitely sensitive to their mechanical environment, which can alter their mitochondrial and cellular function. For example, in bone and cartilage cells fluid-flow induced shear stresses can modulate cytoskeletal dynamics and gene expression profiles. More recently, immune cells were shown to be highly sensitive to hydrostatic pressure. In each of these cases mitochondria were central to these responses. In terms of acute inflammation, mitochondria may have a pivotal role in linking joint tissue injury with chronic disease. These processes could involve the immune cells recruited to the joint, native/resident joint cells that have been damaged, or both. Taken together, these observations suggest that mitochondria are likely to play an important role in linking acute joint tissue injury, inflammation and long-term chronic joint degeneration - and that the process involves mechanobiological factors. In this review, we will explore the links between mechanobiology, mitochondrial function, inflammation/tissue-damage in joint injury and disease. We will also explore some emerging mitochondrial therapeutics and their potential for application in PTOA.